Bacterial Infection Diagnosis and Antibiotic Prescription in 3 h as an Answer to Antibiotic Resistance: The Case of Urinary Tract Infections - Eleonora Nicolai; Massimo Pieri; Enrico Gratton; Guido Motolese; Sergio Bernardini (MDPI AG, 2021)
Current methods for the diagnosis of urinary tract infections with antimicrobial susceptibility testing take 2-3 days and require a clinical laboratory. The lack of a rapid, point-of-care antibiotic susceptibility test (AST) has contributed to the misuse of antibiotics when treating urinary tract infections (UTIs) and consequently to the rise of multi-drug-resistant organisms. The current clinical approach has led to reduced treatment options and increased costs of diagnosis and therapy. To address this issue, novel diagnostics are needed for the timely determination of antimicrobial susceptibility. We present a rapid, point-of-care, phenotypic AST device that can report the antibiotic susceptibility/resistance of a uropathogen to a panel of antibiotics in as few as 3 h by utilizing fluorescent-labelling chemistry and a highly sensitive particle-counting instrument. We analysed 744 urine samples from the outpatients and inpatients of two Italian hospitals. The 130 UTI-positive patient urine samples we found were measured using a panel of six common UTI antibiotics plus a growth control. By comparing our results to hospital laboratory urine cultures, we obtained an overall sensitivity = 81%, a specificity = 83%, an SPV (sensitivity predicted value) = 95%, and an RPV (resistance predicted value) = 54%. According to our preliminary data, the sensitivity predicted value for a single antibiotic agent was 95%, thus allowing (in the vast majority of cases) an early (within 3 h) recognition of an effective agent for a single patient.